2018
DOI: 10.3389/fnhum.2018.00212
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Brain Structural Networks Supports Spatio-Temporal Predictive Processing

Abstract: The ability to generate probabilistic expectancies regarding when and where sensory stimuli will occur, is critical to derive timely and accurate inferences about updating contexts. However, the existence of specialized neural networks for inferring predictive relationships between events is still debated. Using graph theoretical analysis applied to structural connectivity data, we tested the extent of brain connectivity properties associated with spatio-temporal predictive performance across 29 healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…E.g., in catching a ball, joint movements, are arranged in such a way that the hand reaches the target's location at the correct time. These spatial and temporal characteristics of movement are also distinctively represented in the organization underlying cerebral motor control, embedded in both segregated and integrated neuronal circuitries (1, 2). Regarding motor timing, at least two interrelated levels of organization may be discerned:…”
Section: Time and The Brainmentioning
confidence: 99%
“…E.g., in catching a ball, joint movements, are arranged in such a way that the hand reaches the target's location at the correct time. These spatial and temporal characteristics of movement are also distinctively represented in the organization underlying cerebral motor control, embedded in both segregated and integrated neuronal circuitries (1, 2). Regarding motor timing, at least two interrelated levels of organization may be discerned:…”
Section: Time and The Brainmentioning
confidence: 99%
“…Accordingly, the brain is described as a network of nodes and edges, while analytic advancements in network science and statistics allow us to represent and quantify functional interactions among brain regions of interest in order to make inferences about its organizational properties both at rest and as a function of cognitive demands. To our knowledge, a network based description of brain regions integration in timing is still largely incomplete and actually available only in Ciullo et al ( 2018b ) and Ghaderi et al ( 2018 ).…”
Section: Timing In Human and Non—human Animalsmentioning
confidence: 99%
“…Compared to HC, SZD showed the left inferior parietal cortex as less connected to other brain regions (lower D ), even to their neighbors (lower CC node ), resulting in a less efficient information transfer (lower E loc ). The inferior parietal cortex is a multimodal association area intriguingly involved in different cognitive functions [ 65 , 66 , 67 , 68 , 69 ], such as bottom-up attention, lower-order self-perception, undirected thinking, episodic memory, and social cognition, and such functions are notoriously impaired in SZD [ 5 ]. Moreover, several pieces of evidence showed that this area is functionally impaired in undifferentiated samples of SZ (see Torrey, 2007 for a review), being associated with negative symptoms in a functional MRI study [ 70 ], and structurally affected in a volumetric 6-year follow-up longitudinal study [ 71 ] with adolescents at risk of psychosis.…”
Section: Discussionmentioning
confidence: 99%